Cas9‐Cleavage Sequences in Size‐Reduced Plasmids Enhance Nonviral Genome Targeting of CARs in Primary Human T Cells. Issue 7 (19th May 2021) - Jing, Ruirui; Jiao, Peng; Chen, Jiangqing; Meng, Xianhui; Wu, Xiaoyan; Duan, Yanting; Shang, Kai; Qian, Liling; Huang, Yanjie; Liu, Junwei; Huang, Tao; Jin, Jin; et al.
Abstract: T cell genome editing holds great promise to advance a range of immunotherapies but is encumbered by the dependence on difficult‐to‐produce and expensive viral vectors. Here, small double‐stranded plasmid DNA modified to mediate high‐efficiency homologous recombination is designed. The resulting chimeric antigen receptor (CAR)‐T cells display a similar phenotype, transcriptional profile, and in vivo potency to CAR‐T cells generated using adeno‐associated viral vector. This method should simplify and accelerate the use of precision engineering to produce edited T cells for research and clinical purposes. Abstract : In this work, a nonviral site‐specific gene targeting method is developed to make therapeutic chimeric antigen receptor (CAR)‐T cells. The homology repair template in plasmid DNA is flanked by Cas9‐cleavage sequences and the backbone size is reduced to enhance the knock‐in efficiency of CAR in human T cells. This method can produce highly effective CAR‐T cells to kill cancer cells.